Guaianolide–type sesquiterpene lactones from the aqueous extract of Salcedoa mirabaliarum - Quírico A. Castillo,, Pierina E. Vicente, Luis A. Díaz, Tara Sprules, Carime Matos-Espinosa, Yanet Vólquez, (Journal of Applied Pharmaceutical Science, 2024)
The phytochemical study of the aqueous extract of Salcedoa mirabaliarum (aerial parts), afforded five guaianolide– type sesquiterpene lactones: dihydroestafiatone, zaluzanin C, dihydroestafiatol, isoamberboin, and 4–epi– dihydroestafiatol, detected for first time in this species. The chemical structures were identified using 13C Nuclear magnetic resonance by comparison with previously reported data.
Keywords: Salcedoa mirabaliarum, dihydroestafiatone, zaluzanin C, dihydroestafiatol, isoamberboin, 4–epi– dihydroestafiatol